The 5-HT6 receptor antagonist idalopirdine potentiates the effects of acetylcholinesterase inhibition on neuronal network oscillations and extracellular acetylcholine levels in the rat dorsal hippocampus. (August 2016) - Herrik, Kjartan F.; Mørk, Arne; Richard, Nelly; Bundgaard, Christoffer; Bastlund, Jesper F.; de Jong, Inge E.M.
Abstract: The 5-HT6 receptor has emerged as a promising target for cognitive disorders and combining a 5-HT6 receptor antagonist with an acetylcholinesterase inhibitor (AChEI) represents a novel approach for the symptomatic treatment of Alzheimer's disease (AD). A recent phase 2 trial showed that the selective 5-HT6 receptor antagonist idalopirdine (Lu AE58054) improved cognition in patients with moderate AD on stable treatment with the AChEI donepezil. Here we investigated the effects of idalopirdine in combination with donepezil on hippocampal function using in vivo electrophysiology and microdialysis. Network oscillations in the hippocampus were recorded during electrical stimulation of the brainstem nucleus pontis oralis (nPO) in the anesthetized rat and hippocampal acetylcholine (ACh) levels were measured in the freely-moving rat. In addition, potential pharmacokinetic interactions between idalopirdine and donepezil were assessed. Idalopirdine alone did not affect hippocampal network oscillations or ACh levels. Donepezil (0.3 and 1.0 mg/kg i.v.) dose-dependently increased hippocampal theta and gamma power during nPO stimulation. Idalopirdine (2 mg/kg i.v.), administered 1 h prior to donepezil, potentiated the theta and gamma response to 0.3 mg/kg donepezil and prolonged the gamma response to 1 mg/kg donepezil. Donepezil (1.3 mg/kg s.c.) increased extracellular ACh levels in the hippocampus and this was further augmented by administration of idalopirdine (10 mg/kg p.o.) 2 h prior to donepezil. These effects could not be attributed to a pharmacokinetic interaction between the compounds. This study demonstrates that idalopirdine potentiates the effects of donepezil on two pharmacodynamic biomarkers associated with cognition, i.e. neuronal oscillations and extracellular ACh levels in the hippocampus. Such potentiation could contribute to the procognitive effects of idalopirdine observed in donepezil-treated AD patients. Highlights: Idalopirdine augments the effects of donepezil on hippocampal neuronal oscillations. Idalopirdine augments the effect of donepezil on acetylcholine in the hippocampus. 5-HT6 R antagonism augments effects of cholinesterase inhibition in the hippocampus. Idalopirdine potentiates the effects of donepezil on biomarkers for cognition.